Cylindrical battery and design method thereof
By adjusting the relationship between the pole plate and separator thickness of the cylindrical battery, the problem that the internal stress cannot be released during the charging and discharging process is solved, and the diaphragm adapts to expansion and maintains sufficient porosity during the charging and discharging process, which improves the cycle life of the battery and Energy density.
Patent Information
- Application Number
- CN202411738967.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
During the charging and discharging process of cylindrical batteries, due to the expansion and contraction caused by the implantation and disengagement of lithium ions of the positive and negative electrode sheets, the internal stress cannot be effectively released, resulting in a decrease in the porosity of the separator, affecting the migration channel of lithium ions, causing battery polarization and circulation. Lifespan is reduced.
By adjusting the thickness relationship between the electrode sheet and the separator of the cylindrical battery, the specific formula requirements are met, ensuring that the membrane can adapt to the expansion of the negative electrode sheet during the charging and discharging process, maintain sufficient porosity, and ensure the channel of lithium ions. Specific methods include selecting a suitable diaphragm and regulating the selection and compaction density of the negative electrode material to adapt to the thickness variations caused by expansion.
By meeting the specific pole plate and separator thickness relationship, the cylindrical battery can effectively adapt to expansion during charging and discharging, keeping the porosity of the separator within the range of 30~60%, ensuring the channel of lithium ions, avoiding polarization, and improving the circulation of the battery Lifespan and energy density.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery design, and in particular to a cylindrical battery and a design method thereof. Background Art
[0002] With the advancement of science and technology and the improvement of consumers' demands for material life, people have an increasing demand for long-cycle batteries. The electrolyte is the "blood" of the battery and is an important bridge for connecting the positive and negative electrodes to transmit lithium ions. Cylindrical batteries are favored by the market due to their high safety and reliability, but they also face their natural disadvantages - the internal stress cannot be effectively released.
[0003] During the charge and discharge process of lithium-ion batteries, the volume of the positive and negative electrode materials shrinks and expands due to the insertion and extraction of lithium ions from the positive and negative electrodes, which is manifested in the expansion and contraction of the thickness of the electrode sheets. However, due to the unique processing method of cylindrical batteries - winding, the diameter of cylindrical batteries will not change significantly, and thus cannot adapt to the expansion of the electrode sheets during the charge and discharge process. This will cause greater stress inside the winding core due to expansion, thereby compressing the softer diaphragm, and ultimately reducing the porosity of the diaphragm due to the compression of the diaphragm thickness, making it impossible to ensure the migration channel of lithium ions during the battery charge and discharge process, resulting in increased battery polarization and reduced battery cycle life.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a cylindrical battery and a design method thereof.
[0006] The present invention is achieved in that: In a first aspect, the present invention provides a cylindrical battery, wherein the relationship between the pole piece and the separator of the cylindrical battery satisfies the following formula: Ha1+Hc1+2*Hs1= Ha2+Hc2+k*2*Hs2, where Ha1 is the thickness of the negative electrode at 0% SOC, Hc1 is the thickness of the positive electrode at 0% SOC, and Hs1 is the thickness of the diaphragm at 0% SOC; Ha2 is the thickness of the negative electrode at 100% SOC, Hc2 is the thickness of the positive electrode at 100% SOC, and Hs2 is the thickness of the diaphragm at 100% SOC, and k is a coefficient of 0.85~1; Ha1 is 80~160μm, Hc1 is 100~210μm, Hs1 is 12-35μm, Ha 2= Ha1*(1+λ1), λ1 is 5%~30%, Hc2=Hc1*(1+λ2), λ2 is -2%~3%, Hs2 is 6~30μm; σ2 is in the range of 30~60%, σ2= Hs2 / Hs1*σ1, where σ1 is the porosity of the membrane at 0% SOC state, σ2 is the porosity of the membrane at 100% SOC state, and σ1 is 30~60%.
[0007] In an optional embodiment, the active ingredient of the positive electrode sheet is selected from at least one of lithium cobalt oxide, a ternary positive electrode material and lithium iron phosphate.
[0008] In an optional embodiment, the active component of the negative electrode sheet is selected from at least one of graphite, silicon-based materials and lithium titanate.
[0009] In an alternative embodiment, the separator is a polyethylene separator, a polypropylene separator or an electrospun separator.
[0010] In an optional embodiment, the cylindrical battery is an aluminum shell cylindrical battery or a steel shell cylindrical battery.
[0011] In a second aspect, the present invention provides a design method for a cylindrical battery, comprising: (A) Get the expansion rate: Using the positive electrode material and negative electrode material of the target cylindrical battery, a positive electrode sheet and a negative electrode sheet are made according to the surface density and compaction density designed for the cylindrical battery, and the positive electrode sheet and the negative electrode sheet are assembled together with a separator into a laminated battery; Measure the thickness of the positive electrode sheet and the negative electrode sheet of the laminated battery at 0% SOC and 100% SOC, and calculate the expansion rate of the negative electrode sheet λ1=Ha2 / Ha1-1, and the expansion rate of the positive electrode sheet λ2=Hc2 / Hc1-1, wherein Ha1 is the thickness of the negative electrode sheet at 0% SOC, and Hc1 is the thickness of the positive electrode sheet at 0% SOC; Ha2 is the thickness of the negative electrode sheet at 100% SOC, and Hc2 is the thickness of the positive electrode sheet at 100% SOC; (B) Screening membrane: Using the negative electrode material and positive electrode material selected in step (A), select the proposed design thickness of the negative and positive electrodes, which are Ha1 and Hc1 respectively. According to the formula λ1=Ha2 / Ha 1- 1 and λ2=Hc2 / Hc 1- 1 Calculate Ha2 and Hc2; Select a diaphragm with a porosity σ1 of 30-60%, and design a thickness value Hs1. Substitute Hs1 into formula (1): Ha1+Hc1+2*Hs1= Ha2+Hc2+k*2*Hs2, and formula (2): σ2= Hs2 / Hs1*σ1; (C) Result analysis: When k in formula (1) takes any value in the range of 0.85 to 1, the calculated σ2 is in the range of 30 to 60%, and Hs2 is in the range of 6 to 30 μm, it is considered that the design requirements are met, and the proposed design thickness of the positive and negative electrodes and the proposed design thickness of the separator selected in step (B) can be applied to the manufacture of cylindrical batteries; If the values of σ2 and Hs2 do not meet the design requirements, the proposed design thickness value of the separator in step (B) is readjusted until the values of σ2 and Hs2 obtained after being substituted into formula (1) and formula (2) meet the design requirements; or, under the premise that the positive and negative electrode materials and compaction densities remain unchanged, the proposed design thicknesses of the positive and negative electrodes in step (B) are readjusted, Ha2 and Hc2 are calculated, and the design thickness value Hs1 is substituted into formula (1) and formula (2) again until the obtained values of σ2 and Hs2 meet the design requirements; If the values of σ2 and Hs2 do not meet the design requirements, the proposed design thickness value of the separator in step (B) is readjusted, and the values of σ2 and Hs2 cannot meet the design requirements after being substituted into formula (1) and formula (2), then it is necessary to reselect the positive electrode material and the negative electrode material, or reselect the compaction density of the positive electrode material and the negative electrode material, and repeat the operations of step (A) to step (B) until the obtained values of σ2 and Hs2 meet the design requirements.
[0012] The present invention has the following beneficial effects: When the positive electrode sheet, negative electrode sheet and diaphragm of the cylindrical battery provided by the present invention meet the requirements of the above formula, it indicates that during the charge and discharge process of the battery, the diaphragm can adapt to the expansion of the negative electrode sheet. Even if the negative electrode sheet expands and compresses the diaphragm, the porosity of the diaphragm can be ensured to be within the range of 30-60%, thereby ensuring sufficient lithium ion channels and effectively avoiding polarization of the cylindrical battery, thereby ensuring that the battery has a high cycle life and energy density.
[0013] The design method provided by the embodiment of the present invention first selects the positive and negative electrode materials through conventional design methods, designs the surface density and compaction density of the positive and negative electrode materials, and the present invention selects a suitable diaphragm to adapt to the thickness space change caused by the expansion of the negative electrode, thereby ensuring sufficient expansion space and ion channels; since the thickness change caused by the expansion of negative electrode sheets of different materials and different compaction densities during the charging and discharging process is different, the size of the negative electrode expansion can be regulated by adjusting the selection of negative electrode materials or adjusting the compaction density of negative electrode materials, thereby ensuring that the diaphragm of the designed battery has sufficient ion channels during the charging and discharging process. Therefore, the design method provided by the embodiment of the present invention can reduce the stress in the battery and ensure that the diaphragm has sufficient lithium ion channels, thereby improving the polarization of the cylindrical battery, thereby improving the cycle life and energy density of the battery. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0015] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0016] An embodiment of the present invention provides a cylindrical battery, wherein the relationship between the pole piece and the diaphragm of the cylindrical battery satisfies the following formula: Ha1+Hc1+2*Hs1= Ha2+Hc2+k*2*Hs2, where Ha1 is the thickness of the negative electrode at 0% SOC, Hc1 is the thickness of the positive electrode at 0% SOC, and Hs1 is the thickness of the separator at 0% SOC; Ha2 is the thickness of the negative electrode at 100% SOC, Hc2 is the thickness of the positive electrode at 100% SOC, and Hs2 is the thickness of the separator at 100% SOC, and k is a coefficient of 0.85~1 (e.g., 0.85, 0.9, 0.95, or 1); Ha1 is 80~160μm, Hc1 is 100~210μm, Hs1 is 12~35μm (for example, 12μm, 15μm, 20μm, 25μm, 30μm or 35μm), Ha 2= Ha1*(1+λ1), λ1 is 5%~30%, Hc2=Hc1*(1+λ2), λ2 is -2%~3%, Hs2 is 6~30μm; σ2 is in the range of 30~60%, σ2= Hs2 / Hs1*σ1, where σ1 is the porosity of the membrane at 0% SOC, σ2 is the porosity of the membrane at 100% SOC, and σ1 is 30~60% (for example, 30%, 40%, 50% or 60%).
[0017] When the positive electrode sheet, negative electrode sheet and diaphragm of the cylindrical battery provided by the present invention meet the requirements of the above formula, it indicates that during the charging and discharging process of the battery, the diaphragm can adapt to the expansion of the positive electrode sheet and the negative electrode sheet. Even if the positive electrode sheet and the negative electrode sheet expand and compress the diaphragm, the porosity of the diaphragm can be ensured to be within the range of 30-60%, thereby ensuring sufficient lithium ion channels and avoiding polarization of the cylindrical battery, thereby ensuring that the battery has a high cycle life and energy density.
[0018] Optionally, the active ingredient of the positive electrode sheet is selected from at least one of lithium cobalt oxide, ternary positive electrode material and lithium iron phosphate.
[0019] Optionally, the active component of the negative electrode sheet is selected from at least one of graphite, silicon-based materials and lithium titanate.
[0020] Optionally, the separator is a polyethylene separator, a polypropylene separator or an electrospun separator.
[0021] Optionally, the cylindrical battery is an aluminum shell cylindrical battery or a steel shell cylindrical battery.
[0022] An embodiment of the present invention provides a design method for a cylindrical battery, comprising: (A) Get the expansion rate: Using the positive electrode material and negative electrode material of the target cylindrical battery, a positive electrode sheet and a negative electrode sheet are made according to the surface density and compaction density designed for the cylindrical battery, and the positive electrode sheet and the negative electrode sheet are assembled together with a separator into a laminated battery; Measure the thickness of the positive electrode sheet and the negative electrode sheet of the laminated battery at 0% SOC and 100% SOC, and calculate the expansion rate of the negative electrode sheet λ1=Ha2 / Ha1-1, and the expansion rate of the positive electrode sheet λ2=Hc2 / Hc1-1, wherein Ha1 is the thickness of the negative electrode sheet at 0% SOC, and Hc1 is the thickness of the positive electrode sheet at 0% SOC; Ha2 is the thickness of the negative electrode sheet at 100% SOC, and Hc2 is the thickness of the positive electrode sheet at 100% SOC; (B) Screening membrane: Using the negative electrode material and positive electrode material selected in step (A), select the proposed design thickness of the negative and positive electrodes, which are Ha1 and Hc1 respectively. According to the formula λ1=Ha2 / Ha 1- 1 and λ2=Hc2 / Hc 1- 1 Calculate Ha2 and Hc2; Select a diaphragm with a porosity σ1 of 30-60%, and design a thickness value Hs1. Substitute Hs1 into formula (1): Ha1+Hc1+2*Hs1= Ha2+Hc2+k*2*Hs2, and formula (2): σ2= Hs2 / Hs1*σ1; (C) Result analysis: When k in formula (1) takes any value in the range of 0.85 to 1, the calculated σ2 is in the range of 30 to 60%, and Hs2 is in the range of 6 to 30 μm, it is considered that the design requirements are met, and the proposed design thickness of the positive and negative electrodes and the proposed design thickness of the separator selected in step (B) can be applied to the manufacture of cylindrical batteries; If the values of σ2 and Hs2 do not meet the design requirements, the proposed design thickness value of the separator in step (B) is readjusted until the values of σ2 and Hs2 obtained after being substituted into formula (1) and formula (2) meet the design requirements; or, under the premise that the positive and negative electrode materials and compaction densities remain unchanged, the proposed design thicknesses of the positive and negative electrodes in step (B) are readjusted, Ha2 and Hc2 are calculated, and the design thickness value Hs1 is substituted into formula (1) and formula (2) again until the obtained values of σ2 and Hs2 meet the design requirements; If the values of σ2 and Hs2 do not meet the design requirements, the proposed design thickness value of the separator in step (B) is readjusted, and the values of σ2 and Hs2 cannot meet the design requirements after being substituted into formula (1) and formula (2), then it is necessary to reselect the positive electrode material and the negative electrode material, or reselect the compaction density of the positive electrode material and the negative electrode material, and repeat the operations of step (A) to step (B) until the obtained values of σ2 and Hs2 meet the design requirements.
[0023] Preferably, since the negative electrode sheet mainly expands and changes during the charge and discharge process, and the thickness change rate of the positive electrode sheet is smaller, when the calculated results of σ2 and Hs2 do not meet the design requirements, in addition to adjusting the thickness of the diaphragm, the negative electrode is usually adjusted, such as selecting different negative electrode materials and selecting different negative electrode compaction densities to make the σ2 and Hs2 values meet the design requirements.
[0024] It should be noted that in the embodiment of the present invention, the reason why the laminated battery is first assembled for testing is that the laminated battery has no external restraint, and the positive and negative electrodes can expand and contract normally when the battery is charged and discharged, and the accurate electrode thickness can be obtained after the battery is disassembled.
[0025] The design method provided by the embodiment of the present invention first selects the positive and negative electrode materials through conventional design methods, designs the surface density and compaction density of the positive and negative electrode materials, and the present invention selects a suitable diaphragm to adapt to the thickness space change caused by the expansion of the positive and negative electrodes, thereby ensuring sufficient expansion space and ion channels; since the thickness change caused by the expansion of negative electrode sheets of different materials and different compaction densities during the charging and discharging process is different, the size of the negative electrode expansion can be regulated by adjusting the selection of negative electrode materials or adjusting the compaction density of negative electrode materials, thereby ensuring that the diaphragm of the designed battery has sufficient ion channels during the charging and discharging process. Therefore, the design method provided by the embodiment of the present invention can reduce the stress in the battery and ensure that the diaphragm has sufficient lithium ion channels, thereby improving the polarization of the cylindrical battery, thereby improving the cycle life and energy density of the battery.
[0026] Example 1 The positive electrode active layer is composed of lithium iron phosphate, conductive agent (carbon black), and binder (PVDF) in a mass ratio of 97:1:2; The negative electrode active layer is composed of graphite, carbon black, CMC, and SBR in a mass ratio of 95.2:1.5:1.3; The diaphragm is PP film; The battery's design N / P ratio is 1.14.
[0027] The positive electrode design parameters of the experimental group and the comparative example are shown in Table 1: Table 1 Comparison of positive electrode design parameters between experimental group and comparison group
[0028] The negative electrode design parameters of the experimental group and the comparative example are shown in Table 2: Table 2 Comparison of negative electrode design parameters between experimental group and comparison group
[0029] The diaphragm design parameters of the experimental group and the comparative example are shown in Table 3: Table 3 Comparison of diaphragm design parameters between experimental group and control group
[0030] Cylindrical batteries were manufactured according to the parameters of the experimental group and the comparative example, and the capacity retention rate after 1000 cycles and 3000 cycles at 25°C@1C was tested. As shown in Table 4: Table 4 Cyclic performance statistics of experimental group and comparative example
[0031] Example 2 The positive electrode active layer is composed of lithium iron phosphate, conductive agent (carbon black), and binder (PVDF) in a mass ratio of 97:1:2; The negative electrode active layer is composed of graphite, carbon black, CMC, and SBR in a mass ratio of 95.2:1.5:1.3; The diaphragm is PP film; The battery's design N / P ratio is 1.14.
[0032] The positive electrode design parameters of the experimental group and the comparative example are shown in Table 5: Table 5 Comparison of positive electrode design parameters between experimental group and comparison group
[0033] The negative electrode design parameters of the experimental group and the comparative example are shown in Table 6: Table 6 Comparison of negative electrode design parameters between experimental group and control group
[0034] The diaphragm design parameters of the experimental group and the comparative example are shown in Table 7: Table 7 Comparison of diaphragm design parameters between experimental group and control group
[0035] Cylindrical batteries were manufactured according to the parameters of the experimental group and the comparative example, and the capacity retention rate after 1000 cycles and 3000 cycles at 25°C@1C was tested. As shown in Table 8: Table 8 Cyclic performance statistics of experimental group and comparative example
[0036] Example 3 The positive electrode active layer is composed of lithium iron phosphate, conductive agent (carbon black), and binder (PVDF) in a mass ratio of 97:1:2; The negative electrode active layer is composed of graphite, carbon black, CMC, and SBR in a mass ratio of 95.2:1.5:1.3; The diaphragm is PP film; The battery's design N / P ratio is 1.14.
[0037] The positive electrode design parameters of the experimental group and the comparative example are shown in Table 9: Table 9 Comparison of positive electrode design parameters between experimental group and comparison group
[0038] The negative electrode design parameters of the experimental group and the comparative example are shown in Table 10: Table 10 Comparison of negative electrode design parameters between experimental group and control group
[0039] The diaphragm design parameters of the experimental group and the comparative example are shown in Table 11: Table 11 Comparison of diaphragm design parameters between experimental group and control group
[0040] Cylindrical batteries were manufactured according to the parameters of the experimental group and the comparative example, and the capacity retention rate after 1000 cycles and 3000 cycles at 25°C@1C was tested. As shown in Table 12: Table 12 Cyclic performance statistics of experimental group and comparative example
[0041] By comparing the experimental group and the comparative example data of Examples 1 to 3, it can be seen that the experimental group meeting the design requirements of the present invention has better long cycle performance than the comparative group.
[0042] In summary, the cylindrical battery provided by the present invention, whose positive electrode sheet, negative electrode sheet and diaphragm meet the requirements of the above formula, indicates that during the charge and discharge process of the battery, the diaphragm can adapt to the expansion of the negative electrode sheet, and even if the negative electrode sheet expands and compresses the diaphragm, the porosity of the diaphragm can be ensured to be in the range of 30-60%, thereby ensuring sufficient lithium ion channels and avoiding polarization of the cylindrical battery, thereby ensuring that the battery has a high cycle life and energy density.
[0043] The design method provided by the embodiment of the present invention first selects the positive and negative electrode materials through conventional design methods, designs the surface density and compaction density of the positive and negative electrode materials, and the present invention selects a suitable diaphragm to adapt to the thickness space change caused by the expansion of the negative electrode, thereby ensuring sufficient expansion space and ion channels; since the thickness change caused by the expansion of negative electrode sheets of different materials and different compaction densities during the charging and discharging process is different, the size of the negative electrode expansion can also be regulated by adjusting the selection of negative electrode materials or adjusting the compaction density of negative electrode materials, thereby ensuring that the diaphragm of the designed battery has sufficient ion channels during the charging and discharging process. Therefore, the design method provided by the embodiment of the present invention can reduce the stress in the battery and ensure that the diaphragm has sufficient lithium ion channels, thereby improving the polarization of the cylindrical battery, thereby improving the cycle life and energy density of the battery.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cylindrical battery, characterized in that: The relationship between the pole piece and the diaphragm of the cylindrical battery satisfies the following formula: Ha1+Hc1+2*Hs1= Ha2+Hc2+k*2*Hs2, where Ha1 is the thickness of the negative electrode at 0% SOC, Hc1 is the thickness of the positive electrode at 0% SOC, and Hs1 is the thickness of the diaphragm at 0% SOC; Ha2 is the thickness of the negative electrode at 100% SOC, Hc2 is the thickness of the positive electrode at 100% SOC, and Hs2 is the thickness of the diaphragm at 100% SOC, and k is a coefficient of 0.85~1; Ha1 is 80~160μm, Hc1 is 100~210μm, Hs1 is 12-35μm, Ha 2= Ha1*(1+λ1), λ1 is 5%~30%, Hc2=Hc1*(1+λ2), λ2 is -2%~3%, Hs2 is 6~30μm; σ2 is in the range of 30~60%, σ2= Hs2 / Hs1*σ1, where σ1 is the porosity of the membrane at 0% SOC state, σ2 is the porosity of the membrane at 100% SOC state, and σ1 is 30~60%.
2. The cylindrical battery according to claim 1, characterized in that: The active component of the positive electrode sheet is selected from at least one of lithium cobalt oxide, ternary positive electrode material and lithium iron phosphate.
3. The cylindrical battery according to claim 1, characterized in that: The active component of the negative electrode sheet is selected from at least one of graphite, silicon-based materials and lithium titanate.
4. The cylindrical battery according to claim 1, characterized in that: The diaphragm is a polyethylene diaphragm, a polypropylene diaphragm or an electrostatic spinning diaphragm.
5. The cylindrical battery according to claim 1, characterized in that: The cylindrical battery is an aluminum shell cylindrical battery or a steel shell cylindrical battery.
6. A design method for a cylindrical battery, characterized in that: include: (A) Get the expansion rate: Using the positive electrode material and negative electrode material of the target cylindrical battery, a positive electrode sheet and a negative electrode sheet are made according to the surface density and compaction density designed for the cylindrical battery, and the positive electrode sheet and the negative electrode sheet are assembled together with a separator into a laminated battery; Measure the thickness of the positive electrode sheet and the negative electrode sheet of the laminated battery at 0% SOC and 100% SOC, and calculate the expansion rate of the negative electrode sheet λ1=Ha2 / Ha1-1, and the expansion rate of the positive electrode sheet λ2=Hc2 / Hc1-1, wherein Ha1 is the thickness of the negative electrode sheet at 0% SOC, and Hc1 is the thickness of the positive electrode sheet at 0% SOC; Ha2 is the thickness of the negative electrode sheet at 100% SOC, and Hc2 is the thickness of the positive electrode sheet at 100% SOC; (B) Screening membrane: Using the negative electrode material and positive electrode material selected in step (A), select the proposed design thickness of the negative and positive electrodes, which are Ha1 and Hc1 respectively. According to the formula λ1=Ha2 / Ha1-1 and λ2=Hc2 / Hc 1- 1 Calculate Ha2 and Hc2; Select a diaphragm with a porosity σ1 of 30-60%, and design a thickness value Hs1. Substitute Hs1 into formula (1): Ha1+Hc1+2*Hs1= Ha2+Hc2+k*2*Hs2, and formula (2): σ2= Hs2 / Hs1*σ1; (C) Result analysis: When k in formula (1) takes any value in the range of 0.85 to 1, the calculated σ2 is in the range of 30 to 60%, and Hs2 is in the range of 6 to 30 μm, it is considered that the design requirements are met, and the proposed design thickness of the positive and negative electrodes and the proposed design thickness of the separator selected in step (B) can be applied to the manufacture of cylindrical batteries; If the values of σ2 and Hs2 do not meet the design requirements, the proposed design thickness value of the separator in step (B) is readjusted until the values of σ2 and Hs2 obtained after being substituted into formula (1) and formula (2) meet the design requirements; or, under the premise that the positive and negative electrode materials and compaction densities remain unchanged, the proposed design thicknesses of the positive and negative electrodes in step (B) are readjusted, Ha2 and Hc2 are calculated, and the design thickness value Hs1 is substituted into formula (1) and formula (2) again until the obtained values of σ2 and Hs2 meet the design requirements; If the values of σ2 and Hs2 do not meet the design requirements, the proposed design thickness value of the separator in step (B) is readjusted, and the values of σ2 and Hs2 cannot meet the design requirements after being substituted into formula (1) and formula (2), then it is necessary to reselect the positive electrode material and the negative electrode material, or reselect the compaction density of the positive electrode material and the negative electrode material, and repeat the operations of step (A) to step (B) until the obtained values of σ2 and Hs2 meet the design requirements.